Wetting behaviors and interfacial characteristics of molten AlxCoCrCuFeNi high-entropy alloys on a WC substrate. (10th July 2021) - Luo, Wenyan; Liu, Yunzhong; Tu, Cheng
Graphical abstract: Highlights: The wettability of molten Al x CoCrCuFeNi HEAs on a WC substrate was studied. Good wettability with equilibrium contact angles less than 5° was achieved. The adsorption of Cr determines wetting in the initially rapid spreading stage. The wetting of Al x CoCrCuFeNi/WC system in the steady-state stage depends on Al content of the HEA drop. Abstract: The wettability of molten Al x CoCrCuFeNi ( x is from 0 to 1.5, mol.%) high-entropy alloys (HEA) on a WC substrate was measured using a modified sessile drop method at 1823 K in an argon atmosphere. The wetting behaviors and interfacial characteristics between HEAs and WC were studied. Good wettability with final equilibrium contact angles of 0.5°−4.6° is obtained, and addition of Al deteriorates the wettability of the HEAs. The wetting of Al x CoCrCuFeNi/WC system can be roughly divided into an initially sharp spreading stage and a subsequent steady-state phase. In the first stage, the adsorption of Cr atoms at the solid-liquid interface primarily contributes to the wetting, and the contact angle drastically reduces. However, both the wetting behavior and interfacial microstructure are determined by the Al content of the HEA in the next stage. For x ≤ 0.5, the wetting is mainly driven by the dissolution of WC, although a few reaction products of (W, Cr)2 C are observed. Moreover, an obvious dissolution pit appears at the surface of the substrate. When the Al content of x ≥ 1, the interfacial reaction is dominant in competition with the dissolution of WC, and massive reaction products precipitate at the HEA/WC interface, which leads to the formation of a continuous reaction layer.